Analisis Variabilitas Total Nitrogen Tanah dengan Menggunakan Geostatistika pada Lahan Perkebunan Tebu Studi Kasus di Tanggul Kulon Kabupaten Jember - Theresia Novianti Woda; Yagus Wijayanto (Jember University Press, 2023)
Potatoes are a commodity that has high carbohydrates after rice, wheat and paddy which makes potatoes one of the most popular commodities. The high level of seed-borne pathogen infection causes decreased productivity. Tissue culture is one of the methods used to minimize the level of pathogen contamination. The acclimatization phase is a very crucial phase because at this stage it is hoped that potato plants which were previously in in-vitro conditions can adapt to the in-vivo environment. Arbuscular mycorrhizal fungi are fungi that can form a symbiosis with plants. The symbiosis that occurs is that mycorrhizae are able to produce growth hormone which can also help in carrying out nutrient uptake. This experiment was conducted using a factorial Completely Randomized Design (CRD), which consisted of two factors. The first factor is potato cultivar which consists of granola cultivar (K1) and Atlantic cultivar (K2) and the second factor is mycorrhizal dose (M) which consists of 4 levels, namely without mycorrhizal (M0), mycorrhizal dose of 1 gram (M1), mycorrhizal dose of 3 grams (M2), and mycorrhizal dose of 5 grams (M3). The experimental results were analyzed using analysis of variance (ANOVA) and if there was a significant difference, further tests were carried out using the Least Significance Diffent (LSD) test at the 5% level. Based on the experimental results, it was shown that mycorrhizal administration had a significant effect on the parameters of plant height and leaf area. The potato cultivar factor did not have a significant effect on all observation parameters. As well as the treatment of mycorrhizal factors and potato cultivars did not show any interaction on all observation parameters.